FUNDAMENTAL SOLUTION OF THE CAUSHY PROBLEM FOR PARABOLIC SYSTEMS OF SHILOV-TYPE - Унгурян, Галина (SWorldJournal, 2024)
In the paper I consider a new class of parabolic systems of equations with partial derivatives and variable minor coefficients of finite smoothness, which includes the class and class of Petrovsky systems of the first order in the time variable with c